Recovery of heritage software stored on magnetic tape for Commodore microcomputers - Denise de Vries; Craig Harrington (International Journal of Digital Curation, 2017)
Digital games make up a significant but little known chapter in the history of the moving image in Australia and New Zealand.Â  Beginning in the early 1980s, the Australasian software industry developed a remarkable record of content creation. The ``Play It Again'' project is conducting research into the largely unknown histories of 1980s game development in Australia and New Zealand, ensuring that local titles make it into national collections and are documented and preserved, enabling the public to once again play these games.